Cancer RNome: Nature & Evolution - Arora, Mansi (Springer Singapore, 2018)
In the last decade, researchers working in the field of cancer biology have shifted their focus from genetic defects to epigenetic dysregulation, especially that of non-coding RNAs (ncRNAs). This book encompasses a comprehensive review of the transcriptional landscape of the cell and its involvement in the cancer pathophysiology. The first two chapters elucidate the basics of biosynthesis, mechanism of action and modulation of the epigenetic regulation of gene expression by coding as well as non-coding RNAs. The third chapter discusses the aberrant expression of the cellular RNome in the cancer cells and highlights its role in the orchestration of processes involved in evolution as well as the sustenance of cancer cells. The fourth chapter describes the recent advances in the field of translating the transcriptome into diagnostic/prognostic biomarkers and as targets for novel anti-cancer therapies. The final chapter then reviews the emerging experimental approaches to screen, identify and explore the functions of ncRNAs. Providing valuable insights into the field of RNome in the context of cancer, this book is helpful to students, researchers and clinicians.